Pathogenesis-related secondary metabolites in leaves of oil palm seedlings infected with Ganoderma boninense revealed by GC-MS - Syd Ali, Nusaibah; Mohd Rakib, Mohd Rashid (Academic Press, 2026)
Basal stem rot (BSR), caused by Ganoderma boninense , is the most destructive disease of oil palm ( Elaeis guineensis ) in Southeast Asia, severely threatening plantation productivity. A major challenge in BSR management is the prolonged asymptomatic phase, during which the pathogen colonizes host tissues internally for months before visible symptoms appear, limiting opportunities for early intervention. In this study, four-month-old oil palm seedlings were artificially inoculated with G. boninense (UPMGB20) using rubber wood block (RWB) inocula and maintained for six months after inoculation. Despite confirmed pathogen colonization, no visible symptoms were observed at sampling, enabling investigation of host metabolic responses during asymptomatic infection. Untargeted metabolite profiling using gas chromatography-mass spectrometry (GC-MS) identified 16 discriminant metabolites spanning organic nitrogen compounds, prenol lipids, fatty acyls, aromatic derivatives, and organoheterocyclic compounds. Nine metabolites were detected exclusively in infected seedlings, including N1-(4-hydroxybutyl)-N3-methylguanidine acetate and (Z)-9-tricosene, which showed strong associations with pathogen presence. Several metabolites, including phytol, coniferyl alcohol, α-tocopherol, squalene, and benzofuran derivatives, accumulated more than twofold in infected leaves, consistent with enhanced antioxidant activity, lignification-related metabolism, and lipid remodeling under pathogen-induced stress. Principal component analysis (PCA) revealed a clear metabolic distinction between infected and healthy seedlings, with PC1 explaining 59.7% of the total variance. Collectively, these findings indicate that asymptomatic G. boninense infection elicits systemic metabolic reprogramming in oil palm leaves and identify candidate metabolites that may inform the development of leaf-based biochemical indicators for early-stage BSR-associated stress. Further validation under field conditions will be required to assess their utility for integration into practical disease monitoring strategies.